Blood pressure response to exercise in children and adolescents - Alvarez Pitti, Julio; Herceg-Čavrak, Vesna; Wójcik, Małgorzata; Radovanović, Dragan; Brzeziński, Michał; Grabitz, Carl; Wühl, Elke; Drożdż, Dorota; Melk, Anette (Frontiers in Cardiovascular Medicine, 2022)
Blood pressure changes during exercise are part of the physiological response to physical activity. Exercise stress testing can detect an exaggerated blood pressure response in children and adolescent. It is applied for certain clinical conditions, but is also commonly used as part of the assessment of athletes. The interpretation of blood pressure values in response to exercise during childhood and adolescence requires appropriate reference data. We discuss the available reference values and their limitations with regard to device, exercise protocol and normalization. While the link between an exaggerated blood pressure response and cardiovascular events and mortality has been demonstrated for adults, the situation is less clear for children and adolescents. We discuss the existing evidence and propose that under certain circumstances it might be reasonable to have children and adolescents undergo exercise stress testing as a rather non-invasive procedure to add additional information with regard to their cardiovascular risk profile. Based on the existing data future studies are needed to extend our current knowledge on possible links between the presence of certain clinical conditions, the detectability of an exaggerated blood pressure response during childhood and adolescence and the risk of developing cardiovascular morbidity and mortality in later life.
Gesehen am 10.01.2023